Woman’s Resistance Towards Domestic Violence In Anita Shreve’s The Stars are Fire - Dinda Adi Puri (Fakultas Ilmu Budaya, 2025)
This research analyzes a novel by Anita Shreve entitled The Stars Are Fire (2017) as the subject of the study. In the form of qualitative research, this research aims to examine how the discourse of woman’s resistance towards domestic violence is presented in the novel using Stuart Hall’s theory of representation, especially the discursive approach proposed by Michel Foucault. This research also aims to reveal the ideological position of the author of the novel towards the issue of domestic violence. There are two kinds of data in this research. The primary data of this research is taken from dialogues and narrations in Anita Shreve’s The Stars Are Fire novel. Then, the secondary data are the data that are taken from articles, books, interviews, and other sources that are related to the topic of this research. In the analysis process, I do the textual and contextual analysis. The theory of representation by Stuart Hall and the discursive approach by Michel Foucault are used to find the discourse of woman’s resistance towards domestic violence in the novel. The form of domestic violence that is argued by Anne L. Ganley and strategies of resistance argued by Cavanagh are used to help the classification and identification of the issue that happened to the female main character. In doing textual analysis, I also connect it with the contextual background of the story. The textual and contextual analysis is also aimed to uncover the ideological position of the author regarding the issue. This research shows that there are various forms of domestic violence experienced by the female main character of the novel, namely 1) physical abuse, 2) psychological abuse, 3) sexual abuse, and 4) economic abuse. There are various strategies of resistance deployed by woman to stop/reduce the domestic violence, namely, defining and redefining the violence, employing specific strategies for avoiding the violence, active verbal and physical opposition, and leaving the viii relationship. Through the textual and contextual analysis shows that, Anita Shreve, as the author believes in and supports the concept of gender equality.
Reaploud Repository February_Hasyim
Keywords: Woman’s; Resistance